Combined Iron Deficiency and Low Aerobic Fitness Doubly Burden Academic Performance among Women Attending University. Issue 1 (23rd November 2016) - Scott, Samuel P; De Souza, Mary Jane; Koehler, Karsten; Murray-Kolb, Laura E
Abstract: Background: Academic success is a key determinant of future prospects for students. Cognitive functioning has been related to nutritional and physical factors. Here, we focus on iron status and aerobic fitness in young-adult female students given the high rate of iron deficiency and declines in fitness reported in this population. Objectives: We sought to explore the combined effects of iron status and fitness on academic success and to determine whether these associations are mediated by cognitive performance. Methods: Women ( n = 105) aged 18–35 y were recruited for this cross-sectional study. Data were obtained for iron biomarkers, peak oxygen uptake ( V O2peak ), grade point average (GPA), performance on computerized attention and memory tasks, and motivation and parental occupation. We compared the GPA of groups 1 ) with low compared with normal iron status, 2 ) among different fitness levels, and 3 ) by using a combined iron status and fitness designation. Mediation analysis was applied to determine whether iron status and V O2peak influence GPA through attentional and mnemonic function. Results: After controlling for age, parental occupation, and motivation, GPA was higher in women with normal compared with low ferritin (3.66 ± 0.06 compared with 3.39 ± 0.06; P = 0.01). In analyses of combined effects of iron status and fitness, GPA was higher in women with normal ferritin and higher fitness (3.70 ± 0.08) than in those with 1 ) low ferritin and lower fitness (3.36 ± 0.08; P = 0.02) and 2 ) low ferritin and higher fitness (3.44 ± 0.09; P = 0.04). Path analysis revealed that working memory mediated the association between V O2peak and GPA. Conclusions: Low iron stores and low aerobic fitness may prevent female college students from achieving their full academic potential. Investigators should explore whether integrated lifestyle interventions targeting nutritional status and fitness can benefit cognitive function, academic success, and postgraduate prospects.